A boundary elements only solution method for 3D micropolar elasticity. (1st February 2021) - Pierson, Gaël; Kouitat-Njiwa, Richard; Bravetti, Pierre
Abstract: Micropolar elasticity belongs to the class of so-called multi-fields problems. The numerical solution of the associated field equations by the pure boundary element method (BEM) is available only for some 2D geometries. A judicious combination of the local point interpolation method with the pure BEM leads to a pure BEM solution procedure of 3D problems. The effectiveness of the approach is demonstrated on some examples including indentation. A first analysis of the impact of the microstructure on the macroscopic response is presented.